On the analysis of photo-electron spectra - Gao, C. Z.; Dinh, P. M.; Reinhard, Paul-Gerhard; Suraud, E. (Annals of Physics, 2015)
We analyze Photo-Electron Spectra (PES) for a variety of excitation mechanisms from a simple mono-frequency laser pulse to involved combination of pulses as used, e.g.,in attosecond experiments. In the case of simple pulses, the peaks in PES reflect the occupied single-particle levels in combination with the given laser frequency. This usual, simple rule may badly fail in the case of excitation pulses with mixed frequencies and if resonant modes of the system are significantly excited. We thus develop an extension of the usual rule to cover all possible excitation scenarios, including mixed frequencies in the attosecond regime. We find that the spectral distributions of dipole, monopole and quadrupole power for the given excitation taken together and properly shifted by the single-particle energies provide a pertinent picture of the PES in all situations. This leads to the derivation of a generalized relation allowing to understand photo-electron yields even in complex experimental setups.
CRIS-Team Scopus Importer:2023-07-24
Keywords: Photo-absorption spectra; Photo-electron spectra